PENGARUH KEMAMPUAN DAN MOTIVASI TERHADAP KINERJA KARYAWAN PT. MILLENIUM PENATA FUTURES CABANG PEKANBARU - Sundari, Rina (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The aim of this research is to study factors that affecting performance of employee of PT. Millenium Penata Futures branch Pekanbaru. Variables that have been used are including variable Y that is employee performance, and variable X that is capability and motivation. Population and sample in this study is every employees of PT. Millenium Penata Futures branch Pekanbaru with total 45 person. Retrieval of data analysis in this research using descriptive and quantitative methods. Analysis of the data that have been used are validity, reliability test, classic assumption test, multiple linear regression, t-test, f-test, and the coefficient of determination (R2). The results of this study in the regression equation is Y = -0.664 + 0.031X1 + 0.934X2. T test between variable ability (X1) on employee performance (Y) has no significant effect on employee performance. It can be seen from the result that t(calculation) 0.394 < t(table) 2.018, with significant value 0.695> 0.05, while the motivation variable (X2) on employee performance (Y) have significant influence on employee performance. It can be seen from the result that t(calculation) 11.374> t(table) 2.018, with significant value 0.000> 0.05. From the results of test calculations show that f(calculation) 65.324 > f(table) 4.07. With significant value 0.000 <0.005. The coefficient of determination (R2) that was obtained is 0.745 or 74.5%, which means the capability and motivation have major influence on the performance of employees of PT. Millenium Penata Futures Cabang Pekanbaru Branch Pekanbaru. Thus, the initial hypothesis which is capability and motivation give significant influence to the employee performance of PT. Millenium Penata Futures Cabang Pekanbaru Branch Pekanbaru is valid